Multiple fresh fecal microbiota transplants induces and maintains clinical remission in Crohn’s disease complicated with inflammatory mass - He, Zhi (Sci Rep, 2017)
The ancient Chinese medical literature, as well as our prior clinical experience, suggests that fecal microbiota transplantation (FMT) could treat the inflammatory mass. We aimed to evaluate the efficacy and safety of multiple fresh FMTs for Crohn’s disease (CD) complicated with intraabdominal inflammatory mass. The "one-hour FMT protocol" was followed in all patients. Twenty-five patients were diagnosed with CD and related inflammatory mass by CT or MRI. All patients received the initial FMT followed by repeated FMTs every 3 months. The primary endpoint was clinical response (improvement and remission) and sustained clinical remission at 12 months. Secondary endpoints were improvement in size of phegmon/abscess based upon cross-sectional imaging and safety of FMT. 68.0% (17/25) and 52.0% (13/25) of patients achieved clinical response and clinical remission at 3 months post the initial FMT, respectively. The proportion of patients at 6 months, 12 months and 18 months achieving sustained clinical remission with sequential FMTs was 48.0% (12/25), 32.0% (8/25) and 22.7% (5/22), respectively. 9.5% (2/21) of patients achieved radiological healing and 71.4% (15/21) achieved radiological improvement. No severe adverse events related to FMT were observed. This pragmatic study suggested that sequential fresh FMTs might be a promising, safe and effective therapy to induce and maintain clinical remission in CD with intraabdominal inflammatory mass.